Enhancing Audit Quality: Investigating Impact of Audit Fees, Audit Tenure, and Audit Rotation - Putra, Rezzananta Wisnu; Prastiwi, Dewi (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2024)
This research was conducted to investigate improving audit quality through several ways, including audit fees, audit tenure, and audit rotation. This research was conducted by taking a sample of companies in Indonesia listed on the IDX during 2020 to 2022, so 826 data were found. From the course of this research, it was found that audit fees can positively affect audit quality, audit tenure can negatively affect audit quality, and audit rotation can positively affect audit quality. This research contributes to decision making for principals in improving audit quality for the companies they own.